Design of Cascaded H-Bridge Multilevel Inverter Topology for Integrated Portable Power Pack Application - Rosle, Muhammad Luqman Hafiz; Ponniran, Asmarashid; Yatim, Mohd Hafizie (Journal of Electronic Voltage and Application, 2022)
This paper presents the necessity of portable power supplies that can be carried and cater to all the users’ demands. Since the energy storage of the portable power pack are coming from DC supply, it needs an inverter to convert the DC voltage into AC voltage. Most of the low-priced inverters in the market have a simple build and are inefficient, resulting in high THD that can cause the electrical appliance not to work properly. This project was focused on the most suitable inverter type where the cascaded H-bridge multilevel inverter with PWM switching technique was proposed. This type of inverter will produce a better THD and a higher output voltage level when the inverter level is increased. This theory was proved where 3-level, 5-level and 7-level of Cascaded H-Bridge Multilevel Inverter has a 52.05 %, 29.98 % and 21.94 % of voltage THD. These results prove that by increasing the output voltage level can reduce the voltage THD. For the hardware implementation, a 5-Level Cascaded H-Bridge Multilevel Inverter with PWM switching technique is chosen because it has a lower voltage THD compared to 3-Level Cascaded H-Bridge Multilevel Inverter and at the same time use less of semiconductor devices compared to 7-Level Cascaded H-Bridge Multilevel Inverter and has fewer semiconductor losses compared to the inverter with SPWM switching technique. The voltage THD of circuit models hardware when reaches 24 is 28.3 % which is slightly better to simulation result, 29.98 %. This inverter was then connected with a step-up transformer with a ratio of 1:10 to reach standard electrical voltage supply in Malaysia of 230 with a voltage THD of 28.4 % without load and 30 % with load. This proves that the circuit model can work properly as the 5-Level Cascaded H-Bridge Inverter simulation and hardware results show a good agreement.